The Analysis of Power Supply Topologies for Tethered Drone Applications - Wojciech Walendziuk; Piotr Falkowski; Krzysztof Kulikowski (Proceedings, 2020)
This article presents three technical variants of a power supply system of a tethered multirotor drone. The proposed solutions can be applied as power sources for multirotor flying constructions used, among others, for surveillance systems or air quality measurements. The paper describes the topologies of the drones’ supply systems as well as their functional analysis.